Method for preparing dual-responsiveness emulsifier
By preparing dual-responsive emulsifiers, the problems of slow response speed and great environmental impact in the existing emulsions in oil fields are solved, and the adaptability of emulsification at high temperatures, deemulsification at low temperatures, and acidic and alkaline conditions are achieved, and the adaptability of emulsification at high temperatures, etc. is improved. The stability and environmental friendliness of the emulsion are suitable for oilfield production and use.
Patent Information
- Application Number
- CN202310844842.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The stimulus-responsive emulsions used in existing oil and gas fields respond slowly when environmental conditions change, have a large impact on the environment, are weak in stability, and are difficult to meet the multiple environmental adaptation needs of oil field production.
Using a method of preparing a dual responsive emulsifier, by deoxygenating chitosan with [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonate)ammonium hydroxide The reaction was carried out under conditions, an aqueous acetic acid solution was added, and then mixed with an organic solvent to precipitate, extract and dry it to produce an emulsifier with emulsification at high temperature, deemulsification at low temperature, and reversible transformation under acidic and alkaline conditions.
It realizes emulsification at high temperatures and demulsification at low temperatures at oil field sites, adapts to acidic and alkaline conditions, improves the stability and environmental friendliness of the emulsion, and is suitable for oil field production and use.
Smart Images

Figure CN119306888A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field chemicals, and in particular to a method for preparing a dual-responsive emulsifier. Background Art
[0002] As an important energy source, oil has attracted widespread attention from countries around the world, and oil extraction technology has been widely developed. Crude oil becomes thicker and heavier in the third recovery stage, and a large amount of crude oil exists in the pores of the rock, which greatly increases the difficulty of extraction. Emulsification can change the wettability of the rock surface, reduce the oil-water interfacial tension, and thus reduce the viscosity of heavy oil, increase the affected area, reduce the "viscous fingering" phenomenon, and thus increase the recovery rate of crude oil. However, after reaching the surface, the emulsion with good stability is difficult to demulsify quickly, which will delay the subsequent oil-water separation process, is not conducive to transportation and storage, and even accelerates pipeline corrosion and causes safety hazards.
[0003] In order to solve the above problems, stimulus-responsive emulsions have emerged. Stimulus-responsive emulsions refer to intelligent emulsions that can undergo reversible emulsification-demulsification changes by changing their molecular structure when the external environmental conditions change. At present, environmentally responsive emulsifiers mainly include pH-responsive, temperature-responsive, light-responsive, CO2-responsive, magnetic-responsive, redox-responsive, ion-responsive, multi-responsive, and the like. Among them, multiple stimulus responses can not only improve the sensitivity of the emulsion and speed up the response speed, but also adapt to more environmental conditions to achieve intelligent demulsification. However, the current responsive emulsions are mainly concentrated in traditional inorganic and organic molecules (SiO2, Fe3O4, surfactants, etc.), which have a great impact on the environment and the research on emulsion stability is relatively weak. Therefore, the development of green and environmentally friendly multi-stimulus responsive emulsions is of vital importance for the further development of oil fields. Summary of the invention
[0004] One of the present inventions provides a method for preparing a dual-responsive emulsifier, which comprises the following steps:
[0005] 1) adding chitosan and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide into a container, deoxygenating, then adding an aqueous solution of acetic acid, mixing and dissolving, and obtaining a solution;
[0006] 2) adding an aqueous solution of cerium nitrate to the dissolving solution, reacting to obtain a reaction solution;
[0007] 3) mixing the reaction solution and an organic solvent, precipitating, filtering, extracting, and drying to obtain the emulsifier.
[0008] In a specific embodiment, the relative molecular weight of the chitosan is 30,000 to 100,000.
[0009] In a specific embodiment, the deacetylation degree of the chitosan is 97%.
[0010] In a specific embodiment, the mass ratio of the chitosan to the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide is 0.5:1 to 1:1.
[0011] In a specific embodiment, the content of acetic acid in the aqueous solution of acetic acid is 5 wt %, and the mass / volume ratio of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide to the aqueous solution of acetic acid is 1 g:(50 to 80 mL).
[0012] In one embodiment, in step 2), the reaction temperature is 40°C to 60°C.
[0013] In one embodiment, in step 2), the reaction time is 4 to 6 hours.
[0014] In one embodiment, in step 3), the precipitation time is 24 h to 48 h.
[0015] In a specific embodiment, in step 3), the extraction is Soxhlet extraction with an organic solvent.
[0016] In a specific embodiment, the extraction time is 24h to 72h.
[0017] In a specific embodiment, the organic solvent is at least one of acetone, ether and liquid paraffin.
[0018] In a specific embodiment, in step 3), the drying is vacuum drying at room temperature, and the drying time is 48 hours to 72 hours.
[0019] In a specific embodiment, the average particle size of the emulsifier particles is 70 to 300 nm, and the median particle size is 70 to 270 nm.
[0020] In a specific embodiment, the particles of the emulsifier have an average particle size of 74 nm to 295 nm, and a median particle size of 73 nm to 266 nm.
[0021] The second aspect of the present invention provides a composition comprising the dual-responsive emulsifier prepared by the method described in any one of the present inventions, water and liquid paraffin.
[0022] In a specific embodiment, the mass ratio of the water to the liquid paraffin is 1:0.25 to 1:1.
[0023] In a specific embodiment, the mass ratio of the water to the liquid paraffin is 1:0.25, and the mass content of the emulsifier in the composition is 3% to 5%.
[0024] Beneficial effects of the present invention:
[0025] The emulsifier of the invention can realize emulsification at high temperature and demulsification at low temperature, as well as emulsification under acidic conditions and demulsification under alkaline conditions, and is suitable for on-site production conditions in oil fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The experimental flow chart of chitosan grafting PSBMA is shown.
[0027] Figure 2 The infrared spectra of CS3w, SBMA and emulsifier #1 are shown.
[0028] Figure 3 The infrared spectra of CS5w, SBMA and emulsifier #2 are shown.
[0029] Figure 4 The infrared spectra of CS10w, SBMA and emulsifier #3 are shown.
[0030] Figure 5 The results of the emulsion formed by emulsifier 1# being placed in a constant temperature oven at 60°C for 30 days, 60 days and 90 days are shown.
[0031] Figure 6 The results of the emulsion formed by emulsifier 2 being placed in a constant temperature oven at 60°C for 30 days, 60 days and 90 days are shown.
[0032] Figure 7 The results of the emulsion formed by emulsifier 3 being placed in a constant temperature oven at 60°C for 30 days, 60 days and 90 days are shown.
[0033] Figure 8 The results of emulsions formed by emulsifier 1# placed in a constant temperature oven at 20°C, 40°C, 60°C and 80°C for 30 days are shown.
[0034] Fig. 9 The results of emulsions formed by emulsifier 1# placed in a constant temperature oven at 20°C, 40°C, 60°C and 80°C for 30 days are shown.
[0035] Fig.10 The results of emulsions formed by emulsifier 1# placed in a constant temperature oven at 20°C, 40°C, 60°C and 80°C for 30 days are shown. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.
[0037] Example 1
[0038] Synthesis of dual-responsive chitosan-based emulsifiers:
[0039] (1) Weigh 0.6 g of chitosan (CS3w) with a relative molecular weight of 30,000 and a degree of deacetylation of 97% and 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (SBMA) respectively and add them into a three-necked flask. Seal the middle of the flask with a rubber stopper and install glass pistons on both sides of the flask. Perform three vacuum-nitrogen cycle operations on the three-necked flask.
[0040] (2) Add 50 mL of 5 wt% acetic acid aqueous solution into a three-necked flask with a syringe and stir magnetically at 40° C. to obtain a solution after complete dissolution. Dissolve 0.1 g of ammonium cerium nitrate with a small amount of distilled water and inject it into the three-necked flask. React for 6 h to obtain a reaction solution.
[0041] (3) A large amount of acetone was added to the reaction solution for precipitation for 24 hours. The product after filtration was further purified by acetone Soxhlet extraction for 48 hours. Finally, it was placed in a vacuum drying oven and dried at room temperature for 12 hours to obtain a powdered emulsifier 1#.
[0042] Emulsifier 1# was characterized by Fourier transform infrared detection. Using the KBr tablet method, CS3w, SBMA and emulsifier 1# samples were vacuum dried until the mass was constant, and about 200 mg of dried KBr powder and about 2 mg of sample powder were respectively put into an agate mortar and ground until they were a tiny powder of about 2μm, and then pressed into a transparent sheet by a tablet press for detection. The experimental conditions were: resolution 2cm -1 、Wavelength range 500-4000cm -1 The results are shown in Figure 2 .
[0043] from Figure 2 It can be seen that 3420cm -1 The absorption peaks of hydroxyl and amino groups are at 2875 cm -1 The stretching vibration peaks of methyl and methylene are at 1075cm -1 The COC stretching vibration absorption peak of the glucose ring indicates that there is a characteristic peak of chitosan in the molecule. -1 The C=O expansion vibration at 1030 cm -1 The sulfonic acid base at 1550cm indicates that there is a characteristic peak of SBMA in the molecule. -1The absorption peak at the center is the in-plane bending vibration absorption peak of the secondary amide NH, indicating the existence of C=NH structure and the grafting of SBMA onto chitosan.
[0044] Example 2
[0045] The chitosan with a relative molecular weight of 30,000 and a deacetylation degree of 97% in Example 1 was replaced with chitosan with a relative molecular weight of 50,000 and a deacetylation degree of 97% (CS5w).
[0046] The reaction time of step (2) in Example 1 was adjusted from 6 h to 4 h.
[0047] The acetone in step (3) of Example 1 was replaced by ether, and the time for further purification by Soxhlet extraction was adjusted from 48 h to 36 h.
[0048] The other steps were the same as in Example 1 to obtain powdered emulsifier 2#.
[0049] Emulsifier 1# was characterized by Fourier transform infrared detection. Using the KBr tablet method, CS5w, SBMA and emulsifier 2# samples were vacuum dried until the mass was constant, and about 200 mg of dried KBr powder and about 2 mg of sample powder were put into an agate mortar and ground until they were fine powders of about 2μm, and then tableted with a tablet press to obtain transparent sheets for detection. The experimental conditions were: resolution 2cm -1 、Wavelength range 500-4000cm -1 The results are shown in Figure 3 .
[0050] from Figure 3 It can be seen that 3420cm -1 The absorption peaks of hydroxyl and amino groups are at 2875 cm -1 The stretching vibration peaks of methyl and methylene are at 1075cm -1 The COC stretching vibration absorption peak of the glucose ring indicates that there is a characteristic peak of chitosan in the molecule. -1 The C=O expansion vibration at 1030 cm -1 The sulfonic acid base at 1550cm indicates that there is a characteristic peak of SBMA in the molecule. -1 The absorption peak at the center is the in-plane bending vibration absorption peak of the secondary amide NH, indicating the existence of C=NH structure and the grafting of SBMA onto chitosan.
[0051] Example 3
[0052] The chitosan with a relative molecular weight of 30,000 and a deacetylation degree of 97% in Example 1 was replaced with chitosan with a relative molecular weight of 100,000 and a deacetylation degree of 97% (CS10w).
[0053] The reaction time of step (2) in Example 1 was adjusted from 6 h to 5 h.
[0054] The acetone in step (3) of Example 1 was replaced with liquid paraffin, and the time for further purification by Soxhlet extraction was adjusted from 48 h to 36 h.
[0055] The other steps were the same as in Example 1 to obtain powdered emulsifier 3#.
[0056] Emulsifier 1# was characterized by Fourier transform infrared detection. Using the KBr tablet method, CS10w, SBMA and emulsifier 3# samples were vacuum dried until the mass was constant, and about 200 mg of dried KBr powder and about 2 mg of sample powder were put into an agate mortar and ground until they were fine powders of about 2μm, and then tableted with a tablet press to obtain transparent sheets for detection. The experimental conditions were: resolution 2cm -1 、Wavelength range 500-4000cm -1 The results are shown in Figure 4 .
[0057] from Figure 4 It can be seen that 3420cm -1 The absorption peaks of hydroxyl and amino groups are at 2875 cm -1 The stretching vibration peaks of methyl and methylene are at 1075cm -1 The COC stretching vibration absorption peak of the glucose ring indicates that there is a characteristic peak of chitosan in the molecule. -1 The C=O expansion vibration at 1030 cm -1 The sulfonic acid base at 1550cm indicates that there is a characteristic peak of SBMA in the molecule. -1 The absorption peak at the center is the in-plane bending vibration absorption peak of the secondary amide NH, indicating the existence of C=NH structure and the grafting of SBMA onto chitosan.
[0058] test
[0059] 1. Determination of particle size of emulsifier
[0060] Emulsifier 1#, emulsifier 2# and emulsifier 3# are respectively dispersed in deionized water, and dispersed evenly to obtain dispersion liquid of emulsifier 1#, dispersion liquid of emulsifier 2# and dispersion liquid of emulsifier 3#, respectively.
[0061] The three dispersions were added to cuvettes respectively, and the particle size was measured using a dynamic laser particle size analyzer. Each dispersion was measured 5 times and the average and median values were taken. The results are shown in Table 1.
[0062] Table 1
[0063] Emulsifier Average particle size Median particle size Emulsifier 1# 73.7857nm 72.6525nm Emulsifier 2# 197.5499nm 186.3265nm Emulsifier 3# 294.6917nm 265.5418nm
[0064] 2. Determination of graft substitution degree
[0065] The elemental analysis of emulsifier 1#, emulsifier 2# and emulsifier 3# was performed by an elemental analyzer, and the results are shown in Table 2.
[0066] Table 2
[0067] Emulsifier N (wt%) C (wt%) H (wt%) S (wt%) C / N Ratio Emulsifier 1# 7.775161 40.28 6.898 0.178 5.1806 Emulsifier 2# 7.543172 39.121 6.96 0.168 5.18628 Emulsifier 3# 7.456438 38.65 7.107 0.167 5.18344
[0068] Due to the monosubstituted reaction of chitosan, when the substitute contains C and N, the degree of substitution can be calculated according to the following formula (1):
[0069]
[0070] In formula (1), DS is the grafting degree of PSBMA, DD represents the deacetylation degree of chitosan, and M C represents the relative atomic mass of carbon atom (12), M N represents the relative atomic mass of nitrogen atom (14), R represents the C / N ratio in the elemental analysis results in Table 2, and n c / n Represents the ratio of carbon to nitrogen atoms in PSBMA (11).
[0071] The PSBMA grafting substitution degree in emulsifier 1#, emulsifier 2# and emulsifier 3# was calculated according to the element composition test results in Table 2 and formula (1). The results are shown in Table 3.
[0072] Table 3
[0073] Emulsifier Graft substitution degree Emulsifier 1# 36.26% Emulsifier 2# 18.44% Emulsifier 3# 26.72%
[0074] According to the results in Table 3, the PSBMA grafting rates in emulsifier 1#, emulsifier 2# and emulsifier 3# are all positive, indicating that the grafting is successful.
[0075] 3. Determination of emulsion stability
[0076] 3.1 Selection of oil phase
[0077] Take 4 portions of 0.04g emulsifier 1# and disperse them in 7mL deionized water. Add 7mL n-hexane, toluene, liquid paraffin, and thick oil (viscosity is 337mPa·s at 60℃) respectively. Adjust the pH to 2 with HCl. Emulsify at 60℃ with a vortex oscillator at 1000rpm for 5min to obtain the corresponding Pickering emulsion. Observe the emulsion droplets with a metallographic microscope, and measure the particle size of the emulsion droplets with NanoMeasurer software. Keep the Pickering emulsion at 60℃ to observe its stability time. The results are shown in Table 4.
[0078] The above emulsifier 1# was replaced with emulsifier 2# or emulsifier 3#, and the same operation as above was used to observe the stability time of the formed Pickering emulsion and measure the particle size of the emulsion droplets. The results are shown in Table 4.
[0079] Table 4
[0080]
[0081] According to the results in Table 4, it can be seen that emulsifier 3# has the best emulsification performance and liquid paraffin is the best compatible with it.
[0082] 3.2 Ratio selection
[0083] Emulsifier 1#, emulsifier 2# and emulsifier 3# were dispersed in deionized water and liquid paraffin according to the amounts in Table 5, respectively. The pH was adjusted to 2 with HCl. The mixture was emulsified at 60°C with a vortex shaker at 1000 rpm for 5 min to obtain the corresponding Pickering emulsion. The Pickering emulsion was kept at 60°C and its stability time was observed. The results are shown in Table 5.
[0084] According to the results in Table 5, the mass ratio of water to liquid paraffin is 1:0.25, and the emulsifier exhibits a good stabilizing effect when the dosage is 3% to 5%.
[0085] The results of the Pickering emulsion prepared by placing the emulsifier in a constant temperature oven at 60°C for 30 days, 60 days and 90 days are shown in Table 1. Figures 5 to 7 .
[0086] from Figures 5 to 7 It can be clearly seen that although a small amount of oil-water separation occurred at 90 days, the emulsion content was still very high, indicating that the emulsion was relatively stable.
[0087] Table 5
[0088]
[0089] 4. Emulsion response performance
[0090] 4.1 pH response
[0091] Take 0.04g of the emulsifiers of Examples 1 to 3 and disperse them in 11.2mL of deionized water and 2.8mL of liquid paraffin respectively; then add 2mol / L of HCl while shaking to adjust the pH value until it is completely emulsified, which is recorded as the emulsified pH value; then add 2mol / L of NaOH while stirring to adjust the pH value until it is completely demulsified, which is recorded as the demulsified pH value. Complete emulsification under acidic conditions to complete demulsification under alkaline conditions is taken as a cycle, and a total of 5 cycles are tested. The results are shown in Table 6.
[0092] Table 6
[0093]
[0094] 4.2 Temperature response
[0095] 0.04 g of the emulsifiers of Examples 1 to 3 were added to a vial and dispersed in 11.2 mL of deionized water and 2.8 mL of liquid paraffin. The pH was adjusted to 2 with HCl. The mixture was emulsified at 60° C. with a vortex shaker at 1000 rpm for 5 min to obtain the corresponding Pickering emulsion. The Pickering emulsions formed by the emulsifiers of Examples 1 to 3 were placed in an oven at 20° C., 40° C., 60° C., and 80° C., respectively. The emulsion state on the 30th day was observed. The results are shown in Tables 7 and Figures 8 to 10 .
[0096] Table 7
[0097]
[0098] 5. Emulsification properties of emulsions - emulsification index and water separation rate
[0099] 0.04 g of each of the emulsifiers of Examples 1 to 3 was dispersed in 11.2 mL of deionized water adjusted to pH 2 with HCl and 2.8 mL of liquid paraffin, and emulsified at 60° C. with a vortex shaker at 1000 rpm for 5 min to obtain the corresponding Pickering emulsion.
[0100] The obtained emulsion was poured into a 20 mL graduated cylinder and allowed to stand at 60°C. The total height of the liquid surface, the height of the emulsion, and the volume of the precipitated aqueous phase on the third day were recorded. The creaming index (CI) of the emulsion was calculated by formula (2):
[0101]
[0102] Among them, H s Represents the total height of the liquid level, H t Represents the height of the emulsion.
[0103] The smaller the CI of the emulsion, the less the precipitated water phase and oil phase, the larger the amount of emulsion, and the stronger the emulsion stability.
[0104] The separation rate (SR) of the emulsion is calculated by formula (3):
[0105]
[0106] Among them, V sw represents the volume of the precipitated aqueous phase, V w Indicates the volume of deionized water added.
[0107] The smaller the SR value of the emulsion, the smaller the volume of precipitated water and the more stable the emulsion.
[0108] The emulsification index and water separation rate of the emulsion are shown in Table 8.
[0109] According to the results in Table 8, the emulsification index of the emulsion gradually decreases with the increase of temperature, and the water separation rate gradually decreases with the increase of temperature, indicating that the emulsion is stable at high temperature and demulsifies at low temperature.
[0110] Table 8
[0111]
[0112] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.
Claims
1. A method for preparing a dual-responsive emulsifier, comprising the following steps: 1) adding chitosan and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide into a container, deoxygenating, then adding an aqueous solution of acetic acid, mixing and dissolving, and obtaining a solution; 2) adding an aqueous solution of cerium nitrate to the dissolving solution, reacting to obtain a reaction solution; 3) mixing the reaction solution and an organic solvent, precipitating, filtering, extracting, and drying to obtain the emulsifier.
2. The method according to claim 1, characterized in that The relative molecular weight of the chitosan is 30,000 to 100,000.
3. The method according to claim 1, characterized in that: The mass ratio of the chitosan to the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide is 0.5:1 to 1:
1.
4. The method according to claim 1, characterized in that: The content of acetic acid in the aqueous solution of acetic acid is 5 wt %, and the mass / volume ratio of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide to the aqueous solution of acetic acid is 1 g:(50 to 80 mL).
5. The method according to claim 1, characterized in that In step 2), the reaction temperature is 40°C to 60°C; and / or In step 2), the reaction time is 4 to 6 hours.
6. The method according to claim 1, characterized in that In step 3), the precipitation time is 24h to 48h; and / or In step 3), the extraction is Soxhlet extraction with an organic solvent; Preferably, the extraction time is 24h to 72h; Preferably, the organic solvent is at least one of acetone, ether and liquid paraffin.
7. The method according to claim 1, characterized in that In step 3), the drying is vacuum drying at room temperature, and the drying time is 48h to 72h.
8. The method according to claim 1, characterized in that The particles of the emulsifier have an average particle size of 70 to 300 nm and a median particle size of 70 to 270 nm.
9. A composition comprising the dual-responsive emulsifier prepared by the method according to any one of claims 1 to 9, water and liquid paraffin.
10. The composition according to claim 9, characterized in that The mass ratio of the water to the liquid paraffin is 1:0.25 to 1:1; Preferably, the mass ratio of the water to the liquid paraffin is 1:0.25, and the mass content of the emulsifier in the composition is 3% to 5%.
Citation Information
Patent Citations
Carboxymethyl chitosan quaternary ammonium salt and preparation method thereof
CN105254811A
DMDAAC grafted ethoxy chitosan and preparation method thereof
CN107556434A
Method for producing polymer coagulent
KR1019920019675A